Properties of Some Selected Soil under Mymensingh District in Bangladesh - Islam, Md. Tohidul; Islam, Md. Serazul; Hoque, Md Nurul (Journal of Agriculture & Rural Development, 2008)
This paper elucidated an attempt to determine the physical properties of some selected soils at different location under Mymensingh districts. The properties of soils were determined using standard methods. Field moisture content was more or less similar for all the locations. The dry unit weights of selected seven soils for Bangladesh Institute of Nuclear Agriculture (BINA), Valuka, Muktagacha, Trisal, Madhupur, Chorkhai and Shomvoganj sites were found to be 17.61, 16.50, 17.00, 17.50, 15.50, 16.40 and 16.20 kN/m3, respectively while the specific gravities were found as 2.67, 2.66, 2.68, 2.70, 2.69, 2.72 and 2.65, respectively also the values of plastic limits of soils were found to be 16.00, 17.00, 15.50, 18.50, 16.00, 17.20 and 14.00 percent, respectively whereas the plasticity index values were 16.25, 14.50, 15.00, 17.00, 18.00, 13.60 and 15.50 percent, respectively for the above locations. The liquid and plastic limits varied for all the locations but the plasticity index values were found more or less similar for all the soil samples. The friction angles were found more or less similar while cohesion varied for different locations. The properties of soils thus obtained can be used for soils of these areas of Bangladesh. A relation between the gradations with plasticity indices of different soils was also characterized. Key words: Dry unit weights, plastic limits, plasticity index, shear stress and internal friction angle.